Social-Economic Principle in Apportionment of Corporate Profit Tax Paid by Consolidated Group of Taxpayers - Bannova K. A. Kristina Alekseevna; Dolgikh I. N. Irina Nikolaevna; Kropova A. A Alyona Anatoljevna; Pokrovskaya N. V. Nataljya Vladimirovna (2016, 2016)
Title screen